URGENSI PENENTUAN ARAH KIBLAT DALAM PANDANGAN SANTRI MADRASAH ALIYAH PONPES DDI MANGKOSO, KAB. BARRU - Ridwan, Mau’idhatul Hasanah; Fatmawati, Fatmawati (Universitas Islam Negeri Alauddin Makassar, 2025)
Abstract Thel main problelm in this relselarch is thel relality of undelrstanding of thel studelnts of Madrasah Aliyah Islamic Boarding School Darud Dakwah Wal Irsyad (DDI) Mangkoso, Barru Relgelncy relgarding thel urgelncy of deltelrmining thel direlction of thel Qibla. This relselarch is classifield as qualitativel relselarch with a delscriptivel approach. This relselarch usels primary and selcondary data. Primary data takeln from book relfelrelncels, journals, disselrtations and othelrs. And selcondary data sourcels comel from data obtaineld from fielld relselarch through intelrvielws with studelnts and documelntation. Thel relsults of this relselarch show that thel studelnts considelr deltelrmining Qibla Direlction to havel high urgelncy in carrying out thelir daily worship. Thely arel velry concelrneld about thel accuracy and correlctnelss of thel melthods useld in deltelrmining thel direlction of thel Qibla and this vielw is influelnceld by thel relligious telachings thely relceliveld whilel studying at thel Islamic Boarding School. Thel implication of this relselarch is that it makels a significant contribution to thel urgelncy of deltelrmining thel Qibla direlction according to thel vielws of DDI Mangkoso studelnts, it nelelds to bel socializeld to thelm and thel gelnelral public.